The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s40474-018-0137-2
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Tourette Syndrome and Complementary Alternative Medicine

Abstract: Purpose of ReviewTourette syndrome (TS) is a neuropsychiatric condition defined by both motor and phonic tics over a period of at least 1 year with the onset before 18 years of age. The purpose of this article is to review the use of complementary alternative medicine (CAM) in children and adults with Tourette syndrome with emphasis on recent research.Recent FindingsMost patients do not tell their physician about the use of CAM unless if specifically asked. Of the studies reviewed, description of the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Neither of the non-pharmacological and pharmacological treatments results in complete resolution of tic symptoms. Therefore, a variety of seemingly safer and easier complementary alternative medicine (CAM) have become available to the patients with TD and their caregivers (107). Traditional Chinese Medicine (TCM), which mainly includes TCM medication and acupuncture that have been developed for the prevention and treatment of various diseases and refined by the Chinese people over thousands of years, is widely available and commonly used all over China.…”
Section: Traditional Chinese Medicine Treatment Of Td In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Neither of the non-pharmacological and pharmacological treatments results in complete resolution of tic symptoms. Therefore, a variety of seemingly safer and easier complementary alternative medicine (CAM) have become available to the patients with TD and their caregivers (107). Traditional Chinese Medicine (TCM), which mainly includes TCM medication and acupuncture that have been developed for the prevention and treatment of various diseases and refined by the Chinese people over thousands of years, is widely available and commonly used all over China.…”
Section: Traditional Chinese Medicine Treatment Of Td In Chinamentioning
confidence: 99%
“…Neither of the non-pharmacological and pharmacological treatments results in complete resolution of tic symptoms. Therefore, a variety of seemingly safer and easier complementary alternative medicine (CAM) have become available to the patients with TD and their caregivers ( 107 ).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…8 Therefore, patients and their caregivers may turn to complementary and alternative medicine (CAM) in a search for available and effective options because they perceive them as natural and safe. 10 According to the National Center for Complementary and Alternative Medicine (NCCAM), CAM is essentially a group of diverse medical and healthcare practices and products that are considered as a part of "integrative" medicine, which places emphasis on a combined holistic, patient-centered approach to health care and wellness provided through mental, emotional, functional, spiritual, and social aspects. 11 CAM has been widely used for various chronic conditions such as depression, ADHD, anxiety, irritable bowel syndrome, diarrhea, asthma, upper respiratory infections, arthritis, migraines, and musculoskeletal problems.…”
mentioning
confidence: 99%
“…There are only 2 major descriptive studies identifying the frequency and type of CAM used in Tourette syndrome patients reported from USA. 10 In one study, 87.8% of Tourette syndrome patients used nutritional supplements, and a majority of them reported a significant improvement in motor and vocal tics over a 2-month period of using the supplements. 17 Another study reported that about 64% of patients or their caregivers reported using at least 1 CAM therapy and about 80% of CAM users did not ask or inform their doctor before initiating treatment.…”
mentioning
confidence: 99%
“…However, potential side effects and drug-drug interactions have been reported in various anecdotal reports and studies in regard to herbal and nutritional supplements. 3 Therefore, it is necessary for physicians to inquire about complementary and alternative medicine use and educate patient’s caregivers about the significant side effects of certain complementary and alternative medicine therapies and this certainty should be explored in the future studies. We appreciate the discussion and recommendations brought forth by our colleagues.…”
mentioning
confidence: 99%